HUBUNGAN PENGETAHUAN IBU, DUKUNGAN SUAMI DAN EFEK SAMPING DENGAN PENGGUNAAN KONTRASEPSI INTRA UTERINE DEVICE (IUD) DI PUSKESMAS PEDAMARAN TIMUR KABUPATEN OKI TAHUN 2020 - Paula, Yuan (JURNAL SMART ANKES, 2020)
The intrauterine device (IUD) is a small, flexible plastic material that is inserted into the uterine cavity and must be replaced if it has been used for a certain period of time. The purpose of this study was to determine the relationship between Maternal Knowledge, Husband Support and Side Effects with the use of intra-uterine device (IUD) contraceptives at Puskesmas Pedamaran Timur, OKI Regency in 2020. The design of this study used quantitative with a "Cross Sectional" approach. The population was all mothers who were family planning acceptors at the Puskesmas Pedamaran timur, OKI district, totaling 47 respondents. The results of the bivariate research on the relationship between mother's knowledge, husband's support and side effects with the use of intra-uterine device (IUD) contraception showed that based on the Chi-Square statistical test, the knowledge obtained was p value = 0.012, the husband's support got p value = 0.017, side effects obtained p value = 0.003. The results of the study of a total of 47 respondents, there is a relationship between Maternal Knowledge, Husband Support and Side Effects with the use of intra-uterine device (IUD) contraceptives at Pedamaran Timur Health Center, OKI Regency in 2020. As for advice to the Head of Puskesmas Pedamaran timur, it can disseminate information about safe contraception. in society related to the use of long-term contraceptive methods, especially the IUD, so that the method chosen is rational, effective, efficient and in accordance with family planning and the purpose of using contraceptives.